Improving the Social Relevance of Experimental Stroke Models: Social Isolation, Social Defeat Stress and Stroke Outcome in Animals and Humans - Lowry, Chloe A.; Jin, Albert Y. (Frontiers in Neurology, 2020)
The outcome of ischemic stroke varies across socioeconomic strata, even among countries with universal health care. Emerging evidence suggests that psychosocial aspects of low socioeconomic status such as social isolation and social defeat stress interact with, and contribute to, stroke pathophysiology. However, experimental investigations of stroke rarely account for such socioeconomic influences. Social isolation in stroke survivors is associated with increased infarction volume, increased risk of post-stroke depression, and worse long-term functional outcome. Social defeat is thought to contribute significantly to chronic stress in low socioeconomic status groups and is associated with poor health outcomes. Chronic stress is also associated with worse post-stroke functional outcome and greater disability even after accounting for stroke severity, vascular risk factors, and access to acute stroke care. Experimental stroke studies which incorporate social isolation or social defeat stress have shown that both tissue and functional stroke outcome is affected by the increased expression of TNF- and IL-6, increased glucocorticoid production, and suppression of the protooncogene bcl-2. This review explores the consequences of social isolation and social defeat stress on stroke, preclinical stroke models that have been used to investigate these factors, and possible molecular mechanisms underlying the influence of socioeconomic disparities on stroke outcome.